강우 시 중랑천 유역의 수질(T-P, T-N, CODMn, SS, BOD5)변화 특성 - 정재형(Jae Hyung Jung); 조우싱(U Xing Zho); 이태진(Tae Jin Lee); 권오열(O Yul Kwon) (Daehan hwan'gyeong gonghag hoeji, 2014)
Water quality variations were investigated at 4 locations of Jungrang river (upper, middle and lower basins) during a period of 3 rainfall events. During the rainfall, concentrations of $COD_{Mn}$, SS and $BOD_5$ significantly increased, while the concentration of T-N decreased and that of T-P remained relatively constant. This pattern became more apparent as the level of accumulative precipitation and rainfall intensity increased. Simple regression analysis showed that the accumulative precipitation was positively correlated with all water quality pollutants except for T-N. With increasing accumulative precipitation, the concentration of T-N decreased, while the others increased. $R^2$ of simple regressions of hourly average rainfall intensity and water quality pollutants, showed wider range of variation ranged from 0.483 to 0.992, which indicated a strong correlation. The stronger the hourly average rainfall intensity, the more T-N and T-P in the upper basin, more $COD_{Mn}$ in the middle and lower basins, more SS with gradual increase from upper to lower areas, and more $BOD_5$ with gradual decrease from upper to lower region. Simple regression showed that water quality pollution in the upper basin was more sensitive to an increase of rainfall discharge than that in the middle and lower areas. 중랑천 상류에서 하류 방향으로 4개 지점을 선정하여 3회의 강우 사상에 대하여 수질변화 특성을 조사하였다. 강우시 $COD_{Mn}$, SS와 $BOD_5$ 농도는 증가하고, T-N은 감소하고, T-P는 경향성이 뚜렷하게 나타나지는 않았으며, 경향성은 강우량과 강우강도 증가에 따라 더욱 뚜렷하게 나타났다. 누적 강우량과 수질항목별 단순회귀 분석 결과, T-N을 제외하고 전체적으로 양의 상관성을 갖는 것으로 나타나서 T-N은 누적강우량이 커질수록 농도가 감소하는 것으로 나타났고, 다른 항목들은 농도가 증가하는 것으로 나타났다. 시간당 평균 강우강도와 수질항목별 단순회귀분석 결과, $R^2$값이 전체적으로 약 0.483~0.992 범위의 대체적으로 폭 넓은 결정계수를 나타났으며, 강우강도가 강할수록, T-P와 T-N은 상류 유입, $COD_{Mn}$은 중류 및 하류 유입, SS는 상류에서 하류 방향으로의 점진적 증가 유입, 그리고 $BOD_5$는 상류에서 하류 방향으로의 점진적 감소 유입이 되는 것으로 판단되었다. 유량과 수질항목별 단순회귀 분석을 실시한 결과, 중랑천 상류가 유량의 증가와 함께 수질오염도가 민감하게 반응하는 것으로 나타났다.